Decollectivization, Collective Legacy, and Uneven Agricultural Development in China. (October 2017) - Xu, Zhun
Highlights: Collective legacies contribute to Chinese rural development even today. Collective legacies affected the pace of decollectivization in the 1980s. China can learn from its past to address its regional inequality. Summary: China has seen persistent regional inequality in agricultural productivity since it dismantled its rural collectives in the early 1980s. This paper evaluates the effects of collective legacies on the agricultural performance after decollectivization. We construct a Collective Legacy Index (CLI) based on the achievements in the areas of rural infrastructure, education, and health under collectives. Using a district-level panel dataset, we find that the CLI has long-term positive effects on agricultural development after decollectivization. That is, districts that already performed well under socialism could still succeed under a different institution because they had superior infrastructure and human capital. At the same time, districts with less successful experience under socialism are less likely to catch up even after dismantling the collective institutions. The results with an instrumental variable (the pace of decollectivization) further reinforce this conclusion. We therefore argue that different collective legacies contribute to the uneven development in rural China. To tackle its problems of regional inequality, China needs to appreciate the role of its collective legacies in development.